An Optimization Coverage Mechanism in Sensor Networks based on ACO - Ru Huang; Jie Zhu; Guanghui Xu (2007 5th International Conference on Microwave and Millimeter Wave Technology : proceedings : ICMMT 2007 : April 19-21, 2007, Guilin, China, 2007)
In the paper, an energy-efficient Optimization Coverage Mechanism in sensor networks is proposed based on ACO. It can guarantee that each target should be covered by at least one active sensor at the minimum cost, meanwhile, meet the requirement of different coverage accuracy to different levels of targets. To achieve the above mechanism, the novel heuristic factor and global pheromone updating rule are designed, which endow the artificial ants with the ability of coverage-awareness towards the monitored field and energy-awareness towards the sensor area, and finally the optimal robust solution is obtained.